EVALUATION OF HELICOBACTER PYLORI IN PATIENTS INVOLVED TO CHRONIC DYSPEPSIA - H. PARSA; G.H. MUSHTARI (Avicenna Tajik State Medical University, 2020)
Objective: To determine the frequency of Helicobacter pylori (HP) in patients with chronic dyspepsia referred to private laboratories in Mazar-i-Sharif city in 2019. Methods: This study is a descriptive cross-sectional study which the sampling method has performed randomly on six private laboratories in Mazari-Sharif city. The population under study consisted people with digestive disorders and a number of them had no any signs and symptoms. Subjects of study were persons that referred to serological and stool testing for HP at private laboratories in Mazar-e Sharif city in the winter season of 2019. Of course, the patients included in this study are mostly those who have been treated with gastritis tablets at one time but have not been cured. The variants of study included gender, age group, presence and absence of signs and symptoms, place of residence. The patients' information was obtained through the patient record book and patient's examination result sheet in which the blood serum and their stool were used for diagnosis. Results: From 108 patients were recruited for HP study, 53 people were men and 55 people women, who were used for diagnosis serologic and stool tests, which showed that 74% of patients had positive result for HP and 26% negative result for HP and these patients were between the ages of 15-65 in terms of presence and absence of sign and symptoms, 57% with loss of weight and stomach irritation, 14% with anorexia, 7% had headache and vertigo and 22% had no signs and symptoms. Conclusion: The present study on 108 who were referred to private laboratories for blood or stool examination were positive for male (39%) and negative (13%), for female (33%) were positive and (15%) negative. Likewise their age groups were different with the majority of patients being between the ages of 15-25 and the minority were 56-65 years. 57% of patient complaining gastric irritation, severe stomach pain and loss of weight.